OFR-48-75 The Demand For And Supply Of Manpower For The Lead And Zinc Industry In Years 1985 And 2000 ? Summary - Carl R. Christiansen (The National Institute for Occupational Safety and Health (NIOSH), 1975)
The primary objectives of this project are (1) the determination of manpower demand in primary lead and zinc production for the years 1985 and 2000, and (2) the estimation of the availability of the required manpower for these years. In order to meet the first of these objectives relationships between employee requirements and metal production in the various states were established, The total primary lead and zinc production from United states mines in 1985 and 2000 has been predicted by the U.S. Bureau of Mines. These forecasts and the 1974 figures are as follows: [1974 1985 2000 Lead metal, tons 669,000 700,000 900,000 Zinc metal, tons 494,000 585,000 995,000] Mining By analysis of ore reserve data and industry characteristics, the authors estimated the portion of the primary production which each state would yield in the future years. As manpower requirements are determined by the tons of ore produced and by worker productivity, these figures were determined for each mining state and district by developing relationships between lead and zinc metal production, ore production, ore to recoverable metal ratios, employee productivity, and number of employees required. The number of new employees required annually to compensate for attrition and production growth is provided, also.